Phytochemical and chemotaxonomic studies on four plants from genus of Urtica L. (Urticaceae). (February 2023) - Zhang, Xinyi; Lu, Xuan; Feng, Baomin; Xi, Yufei; Gao, Congcong; Feng, Weixing
Abstract: The study aims to conduct phytochemical investigation on four different species of Urtica L., collected in China. The main components of different types of plants in this genus are flavonoids, coumarins, lignans and so on, which are compatible with this study. Eight substances were isolated from Urtica laetevirens Maxim., Urtica mairei Levl., Urtica fissa E. Pritz. and Urtica triangularis Hand-Mass.: one terpenoid (1 ), one coumarin (2 ), four lignans (3 –6 ) and two flavonoids (7 and 8 ). Among them, compound 2 was isolated from all four plants, compounds 1 and 8 were first discovered from Urtica L. In addition, secolignans could be regarded as taxonomic markers for the genus of Urtica L., and its accumulation may be related to its location and altitude. All the above results of the research contributed to consolidating the chemotaxonomic knowledge of Urtica L.. Highlights: A total of eight substances were isolated from four species of Urtica L. Two compounds were obtained from Urtica L. for the first time. Chemotaxonomic significance of these compounds were described. Analyze and speculate the characteristics of the distribution of secolignans. Proving morphology classification is scientific from chemical perspective.